COVID-19 and School Closures - Helena Svaleryd; Jonas Vlachos (Global Labor Organization (GLO), 2022)
To reduce the spread of COVID-19, schools closed to an unprecedented degree in the spring of 2020. To varying extent, students have moved between in-person and remote learning up until the spring of 2021. This chapter surveys the literature on the implications of school closures of primary to upper-secondary schools for virus transmission, student learning, and mental health among children and adolescents in high-income countries. Subject to severe methodological challenges, most studies indicate that the initial school closures at least to some extent contributed to a reduction of virus transmission. However, several studies find that schools could reopen safely, especially when substantial within-school preventive measures were implemented and the general level of transmission was moderate. Student age also matters and keeping schools open for younger students contributes less to overall virus transmission. Most studies find that students learned less and that learning inequalities widened when school closed. These patterns are particularly pronounced for younger students who face more challenges adjusting to remote instruction. Essentially nothing can be said concerning the implications for vocational training. High-quality evidence on the impact on mental health is scarce and the results are mixed, but there are some indications that older students coped better with school closures also in this regard. On balance, closing schools for younger students is less well-motivated than for older students.
Keywords: I12; I21; 330; COVID-19; Mental health; School closures; Student achievement; Virus transmission